Konseling Lintas Budaya Sebagai Bentuk Toleransi dan Kerukunan Antar Umat Beragama di Bandar Pasir Mandoge: indonesia - Muslim, Muslim (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2023)
This research aims to elucidate the concept of cross-cultural counseling and its application in promoting religious tolerance and harmony in Bandar Pasir Mandoge. The research methodology involves a literature review and conceptual analysis, drawing insights from scholarly journals, books, and relevant documents on cross-cultural counseling, tolerance, and interfaith harmony. The findings indicate that cross-cultural counseling is a vital and relevant approach in multicultural societies. Culturally sensitive counselors possessing extensive knowledge and responsive cultural skills can create an inclusive and supportive counseling environment for clients from diverse cultural backgrounds, facilitating effective problem-solving and personal growth. This research highlights the significance of embracing tolerance and respecting differences to foster a peaceful and harmonious society amidst cultural and religious diversity. In conclusion, cross-cultural counseling presents a sensitive and comprehensive approach in promoting interfaith harmony in diverse communities like Bandar Pasir Mandoge. By respecting differences and individual rights to practice their religious beliefs, communities can live in harmony and mutual respect, in line with the spirit of Pancasila as the foundation of the Indonesian nation.